1960
DOI: 10.1152/ajplegacy.1960.199.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of rats and ground squirrels during prolonged lethargic hypothermia

Abstract: After intensive cooling, rats can be maintained at constant body temperature during several hours in a cylinder surrounded by cold water. The rats live in lethargic hypothermia at a body temperature of 15°C for 8–10 hours but can recover only if the hypothermia has not lasted more than 5.5 hours, average time of ‘biological survival.’ After 6 or more hours at 15°C adult rats showed irreversible hemoconcentration, hypoglycemia, drop in arterial blood pressure and low pH of the blood, but no change in pulse rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

1962
1962
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…2 the blood glucose of rats significantly increased during the early phase of hypothermia. This observation is in accord with those of FUHRMAN andCRISMON (1947) andPOPOVIC (1960). The former authors found that the increase in blood glucose was observed only for fed rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 the blood glucose of rats significantly increased during the early phase of hypothermia. This observation is in accord with those of FUHRMAN andCRISMON (1947) andPOPOVIC (1960). The former authors found that the increase in blood glucose was observed only for fed rats.…”
Section: Discussionsupporting
confidence: 91%
“…Blood glucose and free fatty acids are known as the major fuels for shivering thermogenesis, the primary means of heat production in acute cold exposure in rats . Changes in energy substrates for heat production have been investigated for hypothermic homeotherms (FUHRMAN and CRISMON, 1947;PoPoviC, 1960;DEPOCAS, 1962). However, no measurements have been reported on the simultaneous variations in the gas exchange and energy substrates metabolism during hypothermia.…”
mentioning
confidence: 99%
“…The maintenance of vascular tone and generalized mild vasoconstriction may well be one of the important differences between the hypothermed and the naturally hibernating animal. Popovic (1960b), working with rats and ground squirrels, has shown that animals which maintain their blood pressure during the first hours of hypothermia have a better prognosis for long survival. The heart rate in hypothermia is much faster at the same temperature than in an animal entering hibernation, and high blood pressure in the former must be maintained at the expense of a rapidly beating heart.…”
Section: Figurementioning
confidence: 99%
“…These studies, which were performed at temperatures below 30°C, sug gest that hypothermia results in a reduction in the rate of degradation of brain energy metabolism dur ing the onset of hypothermic ischemia as well as a reduced level of brain tissue acidosis compared with normothermic ischemia. However, the clinical application of hypothermia is limited by adverse ef fects associated with level as well as the duration of hypothermia (Popovic, 1960;Michenfelder and Milde, 1977;Bjork and Hultquist, 1960; Brunberg et aI., 1974; Connolly et aI., 1962; Olesen et aI., 1971). …”
mentioning
confidence: 99%